Target of Rapamycin Signaling in Plant Stress Responses. Issue 4 (16th January 2020) - Fu, Liwen; Wang, Pengcheng; Xiong, Yan
Abstract : Recent significant advances allow a more complete understanding of the many functions for TOR signaling in plant responses to different nutrient deficiencies and abiotic stresses. Abstract: Target of Rapamycin (TOR) is an atypical Ser/Thr protein kinase that is evolutionally conserved among yeasts, plants, and mammals. In plants, TOR signaling functions as a central hub to integrate different kinds of nutrient, energy, hormone, and environmental signals. TOR thereby orchestrates every stage of plant life, from embryogenesis, meristem activation, root, and leaf growth to flowering, senescence, and life span determination. Besides its essential role in the control of plant growth and development, recent research has also shed light on its multifaceted roles in plant environmental stress responses. Here, we review recent findings on the involvement of TOR signaling in plant adaptation to nutrient deficiency and various abiotic stresses. We also discuss the mechanisms underlying how plants cope with such unfavorable conditions via TOR–abscisic acid crosstalk and TOR-mediated autophagy, both of which play crucial roles in plant stress responses. Until now, little was known about the upstream regulators and downstream effectors of TOR in plant stress responses. We propose that the Snf1-related protein kinase–TOR axis plays a role in sensing various stress signals, and predict the key downstream effectors based on recent high-throughput proteomic analyses.